2004
DOI: 10.1002/jcp.20013
|View full text |Cite
|
Sign up to set email alerts
|

BRD7, a novel bromodomain gene, inhibits G1–S progression by transcriptionally regulating some important molecules involved in ras/MEK/ERK and Rb/E2F pathways

Abstract: Bromodomain is a 110 amino acid domain. It is evolutionally conserved and is found in proteins strongly implicated in signal-dependent transcriptional regulation. BRD7 is a novel bromodomain gene and it is downexpressed in nasopharyngeal carcinoma (NPC) biopsies and cell lines; its function is poorly understood. In the present study, tet-on inducible expression system was used to investigate the role of BRD7 in cell growth and cell cycle progression. We found that ectopic expression of BRD7 in NPC cells inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 26 publications
3
99
0
Order By: Relevance
“…BRD7 is a novel bromodomain gene that is believed to be involved in signal-dependent transcriptional regulation. Recent data suggest that BRD7 may play a role in certain cancers (Zhou et al, 2004), yet there is no evidence to suggest that it is involved in the etiology of any psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…BRD7 is a novel bromodomain gene that is believed to be involved in signal-dependent transcriptional regulation. Recent data suggest that BRD7 may play a role in certain cancers (Zhou et al, 2004), yet there is no evidence to suggest that it is involved in the etiology of any psychiatric disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Staal et al (2000) reported that BRD7 protein (celtix-1) interacts with interferon regulatory factor 2 in the nucleus and associates with transcriptionally active chromatin in situ. Overexpression of the BRD7 gene in NPC cells is effective to inhibit cell growth and cell cycle progression from G1 to S phase by transcriptional regulation of some cell cycle-related genes (Yu et al 2001;Zhou et al 2004;Peng et al 2006). To better understand the cellular role of the BRD7 gene, in this study, we explored an approach to generate a highly specific BRD7 antibody, and showed that the prepared BRD7 antibody is able to specifically recognize recombinant GST-BRD7N protein and endogenously expressed BRD7 protein.…”
mentioning
confidence: 99%
“…Cell proliferation was promoted by the inhibition of BRD activity in response to calcium signal stimulation (Zhou et al 2004;Korner and Tibes 2008;Sterner et al 1999). It is qualified by the presence of two indicators (CDPK, positive contribution; BRD, negative) in PC-1 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…These indicated that PC-1 (Table 1) and PC-1 (Table 3) were related to the development of the vascular bundle of grafting union. The 7 main indicators of the 17 main indicators in PC-1 (Table 1) and PC-1 (Table 3) (41%) directly were related with calcium signal [POD (Erinle et al 2016), cellulose content (Lin et al 2016), chlorogenic acid content (Ngadze et al 2014), CDPK (Fu et al 2013), CHI , GST (Dulhunty et al 2001), and BRD (Zhou et al 2004)]. Therefore, after grafting, vascular bundle development at the scion may depend on biological responses in which intracellular calcium acts as a second messenger.…”
Section: Discussionmentioning
confidence: 99%